Apolipoprotein-E Gene Polymorphism and Lipid Composition among IUGR and AGA Neonates - Elangovan, Bharathi; N.T, Rajesh; Subrahmanian, Meenu (Journal of Pediatric Genetics, 2021)
Objective The objective of this study is to study the profile of apolipoprotein E (APOE) gene polymorphism and lipid profile among intrauterine growth restriction (IUGR) and appropriate for gestational age (AGA) neonates. This is an observational study. This study was done at the neonatal unit of a teaching hospital in South India. All consecutively born IUGR neonates (cases) of more than 32 weeks' gestational age and AGA neonates (controls) were enrolled for the study. Genomic DNA extraction was done from a total of 102 peripheral venous blood samples. Genotyping of the APOE rs429358 and rs7412 defining the ε2, ε3, and ε4 alleles was done by polymerase chain reaction–restriction fragment length polymorphism method. Prefeed venous blood was collected and analyzed for lipid profile estimation. The allelic frequencies of cases versus control were ε2—9 (8.7%) versus 3 (2.9%); ε3—88 (84.6%) versus 81 (79.4%); and ε4–7 (6.7%) versus 18 (17.6%). The frequency of ε4 isoform allele, associated with adult onset of metabolic diseases was less among the IUGR group. The mean total cholesterol (TC), Low-Density Lipoprotein (LDL), High-Density Lipoprotein, and triglyceride (TG) were 107.59 ± 35.99, 51.69 ± 24.68, 21.75 ± 9.58, and 151.22 ± 61.84 mg/dL, respectively, in the IUGR group. The mean TC and LDL levels in IUGR group were marginally higher than AGA neonates (107 ± 35.99 vs. 100.37 ± 22.69 mg/dL and 51.69 ± 24.68 versus 46.9 ± 19.51 mg/dL, p > 0.05). In both groups, the mean TC and TGL levels were elevated in the ε4 isoform subgroup (p > 0.05). In our study, the ε2 allele was the second most predominant APOE isoform and the ε4 allele of the APOE gene associated with adult-onset diseases was not increased among IUGR neonates. Neonates with ε4 allele showed an abnormal lipid profile in both study groups suggesting a possible association.
Keywords: intrauterine growth restriction neonates; apolipoprotein E gene polymorphism; lipid profile